Bovine hydroxyapatite/3Y-TZP bioceramic: Aligning 3Y-TZP content with sintering parameters - de Azevedo-Silva, Lucas José (2024)
This study aimed to produces and characterize bovine hydroxyapatite (HA) bioceramic with 3Y-TZP addition and analyze different sintering curves. HA was extracted from bovine bones and nanoparticulated. HA discs (0, 1, 5 and 10 wt% 3Y-TZP) were subjected to uniaxial and isostatic pressing. Dilatometry analysis was performed and the groups were sintered using 3 different firing curves (conventional, 1300 °C; 2-step, 1292 °C; 2-step, 1420 °C). The samples were analyzed by X-ray diffraction (XRD), biaxial flexural strength (BFS), Vickers microhardness (VH) and Field emission scanning electron microscopy (FE-SEM). The dilatometry results signaled the need for sintering optimization in groups added with 3Y-TZP. XRD demonstrated the characteristic crystallographic peaks of HA in the pure groups and with 1% 3Y-TZP, and decomposition of HA into β-TCP and formation of calcium zirconate in the groups with 5 and 10% 3Y-TZP. Considering each composition, the groups of pure HA (131.3 ± 13.5 MPa; 401 ± 12.7 GPa) sintered by the conventional curve and HA+1%3Y-TZP (145 ± 8.6 MPa; 507 ± 47.9 GPa), HA+5%3Y-TZP (68.1 ± 14.2 MPa; 183 ± 9.8 GPa) and HA+10%3Y-TZP (55.6 ± 5.1 MPa; 96.1 ± 7.64 GPa) sintered by the 2-step curve at 1420 °C, combined the best BFS and VH results. The addition of 1 wt% 3Y-TZP and optimization in the sintering process improved the mechanical and microstructural properties of HA bioceramics and maintenance of its crystalline characteristics. Refinement in material processing is necessary for the future use of this bioceramic in dentistry.